2010
DOI: 10.1364/ol.35.003946
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of guided-resonances in photonic crystals with aperiodically ordered supercells

Abstract: We report on the first experimental evidence of guided resonances (GRs) in photonic crystal slabs based on aperiodically ordered supercells. Using Ammann-Beenker (quasiperiodic, eightfold symmetric) tiling geometry, we present our study on the fabrication, experimental characterization, and full-wave numerical simulation of two representative structures (with different filling parameters) operating at near-IR wavelengths (1300-1600 nm). Our results show a fairly good agreement between measurements and numerica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Starting from the periodic-approximant case, for which rigorous fullwave numerical modeling is still computationally affordable, in this Section we report the experimental evidence 44 of GR excitation in PCs with aperiodically-ordered supercells based on a quasiperiodic (Ammann-Beenker, octagonal) lattice exhibiting eight-fold symmetry 26 and containing 97 elements.…”
Section: Some Experimental Resultsmentioning
confidence: 99%
“…Starting from the periodic-approximant case, for which rigorous fullwave numerical modeling is still computationally affordable, in this Section we report the experimental evidence 44 of GR excitation in PCs with aperiodically-ordered supercells based on a quasiperiodic (Ammann-Beenker, octagonal) lattice exhibiting eight-fold symmetry 26 and containing 97 elements.…”
Section: Some Experimental Resultsmentioning
confidence: 99%
“…Further studies demonstrated the possibility to excite otherwise uncoupled guided resonances via the judicious introduction of symmetry-breaking point-defects [31] as well as the potential for both sensing and telecommunication applications [32]. Following such theoretical and numerical studies, in 2010, Ricciardi et al provided the first experimental evidence of Fano-type guided resonances in aperiodically-ordered photonic quasicrystal slabs (Ammann-Beenker octagonal tiling) as shown in Figure 1c [33,34].…”
Section: Aperiodic Ordered Structuresmentioning
confidence: 99%
“…Although the works described in the previous sections led to all-in-fiber devices and can therefore be viewed within the lab-on-fiber concept, their main limitations rely on the impossibility to provide a fiber micro-and nano-structuring as well as a functional material definition at the sub-wavelength scale in a controlled manner. This also prevents the exploitation of many novel and intriguing phenomena that are at the forefront of the scientific optical research, involving light manipulation phenomena and excitations of guided resonances in PCs [146,147] and quasi-crystals [148][149][150][151] as well as combined plasmonic and photonic effects in hybrid metallo-dielectric structures [152]. This means that more sophisticated fabrication strategies and technologies need to be used to create the necessary technological scenario for advanced lab-on-fiber components and devices.…”
Section: Towards Advanced Lab-on-fiber Configurationsmentioning
confidence: 99%